2009
DOI: 10.1007/s10549-009-0653-1
|View full text |Cite
|
Sign up to set email alerts
|

Subtypes of familial breast tumours revealed by expression and copy number profiling

Abstract: Extensive expression profiling studies have shown that sporadic breast cancer is composed of five clinically relevant molecular subtypes. However, although BRCA1-related tumours are known to be predominantly basal-like, there are few published data on other classes of familial breast tumours. We analysed a cohort of 75 BRCA1, BRCA2 and non-BRCA1/2 breast tumours by gene expression profiling and found that 74% BRCA1 tumours were basal-like, 73% of BRCA2 tumours were luminal A or B, and 52% non-BRCA1/2 tumours w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
118
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(128 citation statements)
references
References 89 publications
(136 reference statements)
9
118
0
1
Order By: Relevance
“…Several large and integrative research studies based on expression and copy number profiling of familial BC demonstrated molecular heterogeneity of these tumors similar to sporadic tumors, as well these studies defined molecular subtypes based on markers other than BRCA1 and BRCA2 germline status [11,43,44]. Microarray or immunohistochemical analyses demonstrated that approximately three quarters of BRCA1-related BC are BLBC whereas BRCA2 tumors generally cluster within the luminal A or B groups [43,44,45,46] and non-BRCA1/2 with luminal A tumors [11,44].…”
Section: Blbc and Brca1mentioning
confidence: 98%
See 2 more Smart Citations
“…Several large and integrative research studies based on expression and copy number profiling of familial BC demonstrated molecular heterogeneity of these tumors similar to sporadic tumors, as well these studies defined molecular subtypes based on markers other than BRCA1 and BRCA2 germline status [11,43,44]. Microarray or immunohistochemical analyses demonstrated that approximately three quarters of BRCA1-related BC are BLBC whereas BRCA2 tumors generally cluster within the luminal A or B groups [43,44,45,46] and non-BRCA1/2 with luminal A tumors [11,44].…”
Section: Blbc and Brca1mentioning
confidence: 98%
“…Microarray or immunohistochemical analyses demonstrated that approximately three quarters of BRCA1-related BC are BLBC whereas BRCA2 tumors generally cluster within the luminal A or B groups [43,44,45,46] and non-BRCA1/2 with luminal A tumors [11,44].…”
Section: Blbc and Brca1mentioning
confidence: 99%
See 1 more Smart Citation
“…Twosided independent Student's t test without equal variance assumption was used to determine p-values (*, P < 0.05; **, P < 0.01). For analysis of gene expression microarray in primary human breast tumors, box plots and dot plots were performed on three publicly available datasets of BRCA1 mutated breast tumors (van 't Veer et al, 2002;Jönsson et al, 2010;Waddell et al, 2010) and on three sporadic breast tumor datasets (Pawitan et al, 2005;Chin et al, 2006;Sabatier et al, 2011), respectively. Tumor subtype classification was determined as described in each study.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…For example, several observations may be expected to limit the efficiency of the PARP inhibition in BRCA1-and BRCA2-deficient tumors as a synthetic lethal approach. Increase in RAD51 Waddell et al, 2009) and HR can rescue growth defects in BRCA1-deficient cells . Furthermore, the depletion of 53BP1 can rescue BRCA1 deficiency by reactivation of ATM-dependent HR pathway (Bouwman et al, 2010;Bunting et al, 2010).…”
Section: Arrest/senescencementioning
confidence: 99%